Apoptosis of human tongue squamous cell carcinoma cell (CAL-27) induced by Lactobacillus sp. A-2 metabolites - ZHANG, Guoliang (Faculdade de Odontologia de Bauru da Universidade de São Paulo, 2014)
OBJECTIVE: To study the effect of Lactobacillus sp. A-2 metabolites on viability of CAL-27 cells and apoptosis in CAL-27 cells. METHODS: Lactobacillus sp. A-2 metabolites 1 and 2 (LM1 and LM2) were obtained by culturing Lactobacillus sp. A-2 in reconstituted whey medium and whey-inulin medium; the cultured CAL-27 cells were treated with different concentrations of LM1 and LM2 (0, 3, 6, 12, 24, 48 mg/mL) and assayed by methyl thiazolyltetrazolium (MTT) method; morphological changes of apoptotic cell were observed under fluorescence microscopy by acridine orange (Ao) fluorescent staining; flow cytometry method (FCM) and agarose gel electrophoresis were used to detect the apoptosis of CAL-27 cells treated LM1 and LM2. RESULTS: The different concentrations of LM1 and LM2 could restrain the growth of CAL-27 cells, and in a dose-dependent manner; the apoptosis of CAL-27 cells was obviously induced and was time-dependent. CONCLUSIONS: Viability of CAL-27 cells was inhibited by Lactobacillus sp. A-2 metabolites; Lactobacillus sp. A-2 metabolites could induce CAL-27 cells apoptosis; study on the bioactive compounds in the Lactobacillus sp. A-2 metabolites and their molecular mechanism is in progress.